Identification of an inactivating cleavage site for α-thrombin on the heavy chain of factor Va - Erdogan, Evrim; Bukys, Michael A.; Orfeo, Thomas; Mann, Kenneth G.; Kalafatis, Michael (Thrombosis and Haemostasis, 2007)
Previous studies of factor (F)Va inactivation on human umbilical vein endothelial cells have shown that α-thrombin cleaves the heavy chain near the COOH-terminus to produce a Mr 97,000 fragment containing the NH2-terminal portion of the heavy chain and a Mr 8,000 peptide containing the rest of the molecule. The α-thrombin cleavage appeared to occur between amino acid residues 586 and 654 of FV. This region contains a consensus sequence for α-thrombin cleavage located at residues 640–644 (S-S-P-R-S). To test the hypothesis that α-thrombin cleaves the FVa heavy chain at Arg643 and to evaluate the functional importance of this cleavage for FVa inactivation, sitedirected mutagenesis was used to create recombinant FV molecules with mutations R643→Q (FVR643Q) and R643→A (FVR643A). All recombinant molecules were purified to homogeneity and assayed for activity following extended activation with α-thrombin. Under similar experimental conditions, appearance of the Mr 97,000 heavy chain fragment in the plasma and wild-type FVa molecules correlated with partial loss of cofactor activity, while following extended incubation of FVR643Q and FVR643A with α-thrombin no cleavage of the heavy chain at Arg643 was detected and no presence of the Mr 97,000 heavy-chain fragment was noticed. Further, no loss in cofactor activity was observed using these mutant recombinant FVa molecules. Our data demonstrate that cleavage of FVa at Arg643 by α-thrombin results in a partially inactive cofactor molecule and provides for an activated protein C (APC)-independent anticoagulant effect of α-thrombin.
Keywords: Factor Va; α-thrombin; inactivation; heavy chain; coagulation